Microbiological, oxidative stability, physicochemical attributes, and sensory evaluation of beef meatballs with turmeric powder addition - Suharyanto Suharyanto; Warnoto Warnoto; Dwi Ramadanti; Hartati Hartati; Hajrawati Hajrawati (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Meatballs are a popular dish in Indonesia, but they often spoil. To address this, researchers have tried adding natural, low-cost ingredients like turmeric powder. This study tested how different levels of turmeric powder affect meatball quality, including microbes, oxidation, physicochemical traits, and consumer acceptance. The experiment used a completely randomised design with four replications. Treatments were: T0 (no turmeric), T1 (1.5%), T2 (2.5%), and T3 (3.5%), all based on meat weight. Researchers measured total microbes, TBA, cooking yield, tenderness, emulsion stability, moisture content, water-holding capacity, pH, and taste-test scores. Adding turmeric up to 3.5% reduced microbes (by 1 log at 2.5%-3.5%), decreased oxidation, and improved tenderness and emulsion stability. But turmeric also lowered cooking yield, moisture, and pH. Folding test results and water-holding capacity stayed the same at all levels. Panellist preference dropped as turmeric increased.